HAMLET particles in medium : protein fibrils or something else? - Ng, Nicholas Kwok Hing. (2009)
HAMLET, a complex of unfolded α-lactalbumin and oleic acid, kills tumour cells but spares differentiated cells. As HAMLET is a potential anti-cancer drug, mechanism of toxicity needs to be addressed. The HAMLET complex consists of partially unfolded α-lactalbumin with oleic acid and unfolded proteins species have been shown to form amyloid fibres. Using microscopy, particles were observed in mixture of HAMLET in medium. Such particle formations were affected by concentration of HAMLET and its ionic environment. Through this study, I examined the possibility that HAMLET forms protein fibrils. In addition, I investigated the nature of unknown particles formed in HAMLET solution in medium. I have shown that HAMLET fibril formation is unlikely to occur under physiological conditions using spectrometry amyloidal staining techniques and FRET analysis. Those particles shown in media were due to oleic acid and that addition of extra oleic acid promotes further particle formation. Such interactions are likely due to HAMLET having increasingly amphiphatic nature due to its bound oleic acid. In addition, HAMLET combined with debris from dying cancer cells, forming HAMLET positive aggregates visible by confocal microscopy. This is consistent with known high affinity interactions between HAMLET and tumour cells components such as histones. Findings should pose no hurdles to HAMLET clinical testing